Risk of development of visceral metastases subsequent to abiraterone vs placebo: An analysis of mode of radiographic progression in COU‐AA‐302. Issue 8 (6th May 2019) - Teply, Benjamin A.; Qiu, Fang; Antonarakis, Emmanuel S.; Carducci, Michael A.; Denmeade, Samuel R.
Abstract: Background: Abiraterone increases survival in prostate cancer, but tumors resistant to abiraterone can exhibit a hormonally resistant, aggressive phenotype. We hypothesized that the therapeutic pressure of abiraterone is resulting in more clinically aggressive disease at progression, characterized by increased visceral metastases. Our objective was to determine whether abiraterone increased the risk of development of visceral metastases at the time of progression compared with placebo in a randomized phase III trial. Methods: We performed a post hoc analysis of the COU‐AA‐302 trial of abiraterone plus prednisone vs placebo plus prednisone in patients with metastatic castration‐resistant prostate cancer. The primary outcome was the development of visceral metastases. The cumulative incidences of visceral metastases were calculated by the Kaplan‐Meier method and compared using log‐rank testing. Multivariable Cox regression analysis assessed for the independent association of abiraterone with the development of visceral metastases. Results: Eighty‐four of 1088 patients developed visceral metastases during study. Log‐rank testing and Cox regression showed no difference in time to visceral metastases between groups (HR 1.01 [95% confidence interval (CI), 0.65‐1.56]; P  = .97). Abiraterone treatment was not associated with the development of visceral metastases in multivariable analysis (HR 0.89 [95% CI, 0.57‐1.40]; P  = .62). The study was limited by censoring of radiographic outcomes at the time of completion of primary study therapy; longer term risks were not assessed. Conclusions: Abiraterone was not associated with increased risk of visceral metastatic disease at the time of progression compared with placebo.